Customary Authority in the Deduaian Tradition of Lampung Saibatin Marriage from Islamic Legal Perspectives - Annisa Saraswati; Linda Sari Bulan Siregar; Wensislaus Parut (USRATY : Journal of Islamic Family Law, 2024)
This research aims to examine the role of customary authority in the Deduaian tradition within the Lampung Saibatin marriage system in Bandar Lampung, Indonesia, and to analyze its meaning from Islamic legal perspectives. The study employs a qualitative approach with field research design, using an interpretive-analytical orientation in which data are collected and interpreted directly from the research setting through observation, interviews, and documentation. The findings reveal that the Deduaian tradition is structured through a sequence beginning with family agreement and permission from inner customary leaders, followed by systematic notification to the community, traditional leaders, religious figures, and government representatives through door-to-door communication, and continuing with a ritual bathing procession at Batanghari River involving female customary representatives from the Mena, Dukhi, Kanan, and Kikhi tribes who escort the bride-to-be in a closed ceremonial setting before she is dressed in traditional attire and paraded to the wedding house under customary supervision. The study concludes that the Deduaian tradition functions as a living customary practice (‘urf) that is socially recognized and continuously practiced, operating within the boundaries of Islamic legal permissibility while reinforcing customary governance and social order. This research contributes to the preservation of the deduaian process through stories and traditional ceremonies among the people of Lampung. It also emphasizes the importance of safeguarding cultural heritage and promotes cross-cultural understanding at a global level.